HIPNO MOTIVASI - M.Insan Romadhan (JPM17: Jurnal Pengabdian Masyarakat, 2017)
Learning achievement is the maximum benchmark that has been achieved after thestudents do learning activities for a predetermined time. Motivation to learn is apsychological condition that encourages a person to do learning activities. From thesemotivations will encourage a student to continue learning in order to achieve theexpected goal of achievement in learning. Learning achievement is also determinedby the discipline in learning. Which means the ability to self-direct students bothmental and physical that takes place in the active interaction for learning activities inaccordance with the rules made by the school and the students themselves.